Kebijakan Diaspora India di Asia Tenggara: Corak Strategi Ekonomi dalam Ikatan Identitas Budaya - Azizi, Naufal (Paradigma: Jurnal Kajian Budaya, 2014)
The paper describes the economic influence in the cultural policy seen through the big number of the diaspora of ethnic and national of India in Southeast Asia. Although in one hand, the India diaspora is one of the substantial sources in developing India, however, on the other, there are some obstacles found in this matter, such as that the Indian policy is partial against other countries in Southeast Asia, so as that the countries of Southeast Asia partial against the Indian diaspora. The writer of this paper, starts his argument with the idea to offer double citizenship to the Indian migrants, and then seeing in social perspective the Indian cultural identity in Southeast Asia. Besides this, the writer brings to highlight the bilateral relation between India and Indonesia and last is the importance of how the Indian government places itself among the Southeast Asian countries, which may become a way of approach the countries of Southeast Asia encounter the migrants of India.